Antinociceptive effect of amikacin and its interaction with morphine and naloxone - (:unkn) unknown (ACADEMIC PRESS LTD, 2000)
Amikacin sulphate (30 mg kg(-1)) administered:either intraperitoneally (i.p.) or subcutaneously (s.c.) produced antinociceptive effect in BALB/c mice in the acetic acid writhing test which is employed as an inflammatory pain model. The lack of difference between two routes with ri:gard to antinociceptive potency was taken as evidence for the absence of a local effect. Amikacin sulphate-induced antinociception seems unlikely to be due to non-specific behaviour alteration, since this drug, at a dose range of 15-100 mg kg(-1) did not affect motor coordination of mice in rot-a-rod test. Morphine (1 mg kg(-1)) also caused antinociception when administered i.p. or s.c. but the effect was greater with the latter route. At the i.p. site; the concurrent use of amikacin and morphine produced more remarkable antinociception compared to their individual usages. Besides, naloxone (2 mg kg(-1)) significantly decreased antinociceptive effect of amikacin but itself also exerted antinociception. At present, we have no plausible explanation for these findings at the i.p. site. (C) 2000 Academic Press.
Keywords: amikacin sulphate; opioids; writhing test; BALB/c mice; ADMINISTERED AMINOGLYCOSIDE ANTIBIOTICS; CALCIUM-CHANNEL BLOCKERS; DIFFERENTIAL SENSITIVITY; DIVALENT-CATIONS; OPIOID AGONISTS; FORMALIN TEST; N-TYPE; MICE; ANALGESIA; PAIN